Oral Clonidine: A Simple, Effective and Safe Sedative Agent for Hemodynamic Stability during Laparoscopic Surgery and a Calm Post-surgical Phase - Ketaki Marodkar (Achievements and Challenges of Medicine and Medical Science Vol. 6, 2024)
Background: Laparoscopic surgery is the quintessence of modern surgical practice due to its cosmetic scar, early ambulation, less mortality (less than 0.1%), and less compromised postoperative respiratory and gastro-intestinal functions. Carbon dioxide pneumoperitoneum (PNP), the hallmark of laparoscopic surgery and patient positioning leads to significant hemodynamic changes in laparoscopic surgeries. Laparoscopy is the essence of modern surgery but the carbon dioxide pneumoperitoneum used therein significantly impairs patient’s cardiopulmonary function. Clonidine, by its central sympatholysis, reduces perioperative hemodynamic instability and also has multiple added advantages in the post-operative period. Methods: In this prospective, randomized, double-blind, placebo-controlled study on 60 ASA I/II patients, clonidine 150 \(μ\)g for weight <55 kg and 200 \(μ\)g for weight >55 kg was administered per oral to 30 patients (clonidine group) 90 minutes before induction of general anaesthesia and intra-operative haemodynamics were monitored at specific time periods and compared with the placebo group patients (n=30) who received oral vitamin C. The tablet Arkamin (100 \(μ\)g/ tablet), manufactured by Unichem laboratories, India for pre-medicating all the patients in the clonidine group, was used. A pre-operative anxiety score, post-operative sedation and pain scores and the presence of nausea-vomiting, shivering and dry mouth at the end of the first and sixth postoperative hours, were noted. An \(α\) error of 0.05 and power of study 80% after permitting \(β\) error of 0.2 was assumed. Results: Clonidine group patients remained haemodynamically stable throughout the intra-operative period. In the clonidine group, less number of patients required fentanyl for tachycardia (1 vs 11) and NTG for hypertension (none vs 7). Similarly, the pain and anxiety scores were significantly less in clonidine group patients. At the end of the first postoperative hour incidence of pain, shivering and vomiting in the placebo group was 33%, 36% and 20% respectively whereas in the clonidine group incidence was 6%, 0 and 0. At the end of 6 post-operative hours, the incidence of pain and vomiting was 73% and 36% in the placebo group whereas it was 10% and 0 in the clonidine group. Conclusions: Oral clonidine in the present dose is able to maintain stable intra-operative haemodynamics and achieve a calm post-operative period during laparoscopic surgeries in ASA I/II patients. Further studies are needed to confirm its safety in elderly patients and patients with compromised cardiovascular function.